How solidarity can change the world : a handbook of socialist politics - Engels, Friedrich; Kautsky, Karl; Luxemburg, Rosa; Trotski, Leon; Matgamna, Sean (London : Alliance for Workers' Liberty, 1998)
Bibliotheek François Vercammen
Themanummer van Workers' Liberty, nrs. 46-47, April 1998
Engels
Monografie
Keywords: communisme